Analysis of fresh frozen plasma utilization indications in children: An audit of a tertiary care hospital in Turkey. (December 2022) - Gürlek Gökçebay, Dilek; Turgutoğlu Yılmaz, Aslı; Şantaflıoğlu, Beytullah; Becerir, Cem; Tayman, Cüneyt; Yarali, Nese; Yasar Özbek, Namık
Abstract: Background: Although indications of fresh frozen plasma (FFP) usage are limited to certain circumstances in children, there is an increasing trend towards inappropriate usage are reported in clinical practice. The aim of this study was to evaluate the appropriateness of pediatric FFP utilization in our tertiary care hospital. Methods: This prospective observational study was conducted at a tertiary care academic pediatric hospital. All FFP orders were evaluated for appropriateness over a 4-monts period by 2 hematologists. Data collected include demographic information, diagnosis, FFP transfusion indication, pre-transfusion coagulation tests, surgical procedure or bleeding status, and transfusion reactions. Results: Three hundred twenty-four patients (57 % males, 43 % females) were transfused in 987 episodes. The mean age of the patients was 5.4±5.7 years. The majority of the patients (33 %) were under 1 y of age and the products were primarily utilized by pediatric and cardiovascular intensive care units. Pre-transfusion coagulation testing was only available in 674 (68 %) of the transfusion episodes. The rate of appropriate FFP transfusion episodes was 59 % (587/987). Inappropriate usage was mostly related to sepsis and minor coagulation abnormalities without bleeding. The higher rates of inappropriate transfusion orders were observed in pediatric and neonatal intensive care units, and hematology/oncology departments. Conclusions: Inappropriate use of FFP in children remains a significant challenge. The regular audit and sustainable education programs targeting the efficient use of FFP for health professionals at the national level can improve transfusion practices.